Digitalized bioeconomy: Planned obsolescence-driven circular economy enabled by Co-Evolutionary coupling. (February 2019) - Watanabe, Chihiro; Naveed, Nasir; Neittaanmäki, Pekka
Abstract: Driven by digital solutions, the bioeconomy is taking major steps forward in recent years toward achievement of the long-lasting goal of transition from a traditional fossil economy to a bioeconomy-based circular economy. The coupling of digitalization and bioeconomy is leading towards a digitalized bioeconomy that can satisfy the shift in consumers' preferences for eco-consciousness, which in turn induces coupling of up-down stream operation in the value chain. Thus, the co-evolution of the coupling of digitalization and bioeconomy and of upstream and downstream operations is transforming the forest-based bioeconomy into a digital platform industry. Aiming at addressing this transformation, a model was developed that explains above mentioned dynamism and demonstrated its reliability through an empirical analysis focusing on the development trajectory of UPM (forest-based ecosystem leader in Europe and a world pioneer in the circular economy) over the last quarter century, highlighting its efforts towards planned obsolescence-driven circular economy. It was comprehended that with the advancement of digital innovations, UPM has incorporated a self-propagating function that accelerates digital solution. Furthermore, this self-propagating function was triggered by coupling with a downstream leader, Amazon, in the United States. The dynamism in transforming a forest-based bioeconomy into a digital platform industry is thus clarified, and new insights common to all industries in the digital economy are provided. Highlights: Metabolism enabling forest-based ecosystem leader in Europe UPM's resurgence was analyzed. Dynamism in transforming a forest-based bioeconomy into a digital platform industry was analyzed. A model tracing the transforming dynamism was developed and its reliability was demonstrated. Planned obsolescence-driven circular economy initiated by the world leader UPM was analyzed. Significance of co-evolution between digital-bio and up-down stream coupling was demonstrated.